Prevention of Early Birth in Pregnant People with Kidney Disease - Suyarkulova Madhiya Erkinovna; Abdullaeva Muazzam Rustamjon kizi (Zien Journals, 2022)
The rate of kidney damage during pregnancy is generally declining worldwide, but remains an important health problem in developing countries. It is also possible that the woman was diagnosed with kidney disease for the first time. Understanding what normal physiological changes in pregnancy are is crucial in diagnostic evaluation. This article discusses the relationship between kidney disease and pregnancy. Discussions included physiological changes in normal pregnancy in a patient with kidney disease and anomalies that occur during pregnancy, the impact of pregnancy on kidney disease, as well as the impact of kidney disease on pregnancy.
Keywords: kidney disease; urinary system; gestational age; clinical manifestations